Phytochemical investigation and in vitro antimicrobial activity of Richardia scabra (Bangladesh Journal of Pharmacology, 2016)
The present study was aimed to evaluate the phytochemical screening and antimicrobial activity of the petroleum ether and methanol extracts from the mature leaves of Richardia scabra from India. Disc diffusion method was used to determine the zone inhibition of the tested samples for antibacterial and agar plug method was used to determine the antifungal activity, while the microtube-dilution technique was used to determine the minimum inhibitory concentration. Both extracts showed significant antibacterial and antifungal activities when tested against 10 bacterial and four fungal strains. The minimum inhibitory concentrations of the methanol extract of R. scabra ranged between 12.5100 ?g/mL for bacterial strains. Alkaloids, steroids, flavonoids, fatty acids, terpenoids and simple sugar were detected as phytoconstituents of extracts. To the best of our knowledge, this is the first report against antimicrobial activity of common weed species R. scabra found in India.